2011
DOI: 10.1007/978-3-642-23774-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Elderly User Evaluation of Mobile Touchscreen Interactions

Abstract: Abstract. Smartphones with touchscreen-based interfaces are increasingly used by non-technical groups including the elderly. However, application developers have little understanding of how senior users interact with their products and of how to design senior-friendly interfaces. As an initial study to assess standard mobile touchscreen interfaces for the elderly, we conducted performance measurements and observational evaluations of 20 elderly participants. The tasks included performing basic gestures such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(128 citation statements)
references
References 13 publications
10
114
3
1
Order By: Relevance
“…Leonardi et al found that seniors preferred intuitive touchscreen interfaces over keyboards [ 19]. Kobayashi et al reported that mobile touchscreen interactions are "enjoyable" for seniors and their skills with such interfaces improve rapidly [ 20]. Those studies motivated us to include touchscreen devices in the primary targets of It seems acceptable.…”
Section: Senior-friendly Systems What Assists and Hinders The Use Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Leonardi et al found that seniors preferred intuitive touchscreen interfaces over keyboards [ 19]. Kobayashi et al reported that mobile touchscreen interactions are "enjoyable" for seniors and their skills with such interfaces improve rapidly [ 20]. Those studies motivated us to include touchscreen devices in the primary targets of It seems acceptable.…”
Section: Senior-friendly Systems What Assists and Hinders The Use Ofmentioning
confidence: 99%
“…It is known that senior people have trouble in using the keypad on mobile phones, particularly on a touchscreen [ 20]. The problem is more serious in East Asia, where frequent mode-switching is required to access thousands of characters.…”
Section: Question-answer Cardsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Holzinger, Searle & Wernbacker (2001) suggest that an important factor to consider is an individual's previous exposure to technology, known as the PET factor. Studies have shown that older adults are less likely to use technology than the younger generation (Caprani,et al 2012) but short periods of practice can result in proficiency (Kobayashi, Hiyama, Miura, Asakawa, Hirose et al (2011).…”
Section: Limitationsmentioning
confidence: 99%
“…1, include home, summary, and graph views that handle functions that log the sensor values, display walk summaries for the entire period of use of the application, and show detailed results. The design of these views, including button and font sizes, was developed by consulting the Apple iOS Human Interface Guidelines and a guideline for seniors proposed by Kobayashi et al [1,32]. To avoid confusion, the interface can be operated only by tapping a few buttons.…”
Section: Interfacesmentioning
confidence: 99%